Correlation of Expression Levels of Copper Transporter 1 and Thymidylate Synthase with Treatment Outcomes in Patients with Advanced Non-small Cell Lung Cancer Treated with S-1/Carboplatin Doublet Chemotherapy - Konishi, Maho; Imai, Asuka; Fujii, Masanori; Sugimoto, Keisuke; Katakami, Nobuyuki; Imai, Yukihiro; Kamoshida, Shingo (Asian Pacific journal of cancer prevention : APJCP, 2018)
Background: Copper transporter 1 (CTR1) is a critical determinant of the uptake and cytotoxic effect of the platinum drugs carboplatin and cisplatin. Thymidylate synthase (TS) is an enzyme involved in DNA synthesis and is associated with resistance of tumor cells to 5-fluorouracil. We investigated the correlation between CTR1 and TS expression levels and treatment outcomes in patients with advanced non-small-cell lung cancer (NSCLC) treated with S-1/carboplatin doublet chemotherapy. Methods: Twenty-nine patients were enrolled in this study. Tumor expression of CTR1 and TS was measured immunohistochemically and analyzed for correlation with tumor response, progression-free survival (PFS), and overall survival (OS). Results: Tumor response was significantly better in patients with CTR1High tumors than in patients with CTR1Low tumors (64% vs. 18%, P = 0.02). Patients with TSLow tumors had a significantly longer OS (median 21.2 vs. 8.5 months, P = 0.02), but not PFS, than patients with TSHigh tumors. When CTR1 and TS co-expression was analyzed, patients with either CTR1High or TSLow tumors showed a significantly better tumor response (50% vs. 0%, P = 0.01), longer PFS (median 4.2 vs. 2.1 months, P = 0.03), and longer OS (median 21.2 vs. 8.5 months, P = 0.01) than patients with both CTR1Low and TSHigh tumors. Conclusions: Our study suggests that combined CTR1/TS expression status has the potential to be an important predictor of good treatment outcomes in patients with advanced NSCLC treated with S-1/carboplatin doublet chemotherapy.